Portuguese Version of the Infertility Self-Efficacy Scale [Escala de Auto-eficácia para Lidar com a Infertilidade (ISE-P)] - Galhardo, Ana (2013)
CHARACTERIZATION: is a selfreport instrument aimed at assessing infertile patients’ perception of their capability to use their own cognitive, emotional, and behavioral abilities for dealing with the infertility diagnosis and medical treatment. || STRUCTURE AND SCORING: Subjects are asked to rate on a 9-point scale the degree in which they think they feel confident. The 16 items converged in a single-component of ‘‘cognitive/affect regulation’’ accounting for 55.55% of total variance. The answer to the items is on an ordinal scale, in Likert format, of nine positions, from 1 = Absolutely not confident to 9 = Totally confident. || PSICOMETRIC CHARACTERISTICS: The ISE-P presented an excellent internal consistency, with a Cronbach alpha of 0.96. Significant differences were found between men and women (t = 6.95; p < 0.001). Men presented higher levels of self-efficacy to deal with infertility (M = 106.05; SD = 21.92) when compared to their female partners (M = 86.49; SD = 25.21).